Optimization of Norbornadiene Compounds for Solar Thermal Storage by First‐Principles Calculations. Issue 14 (2nd June 2016) - Kuisma, Mikael; Lundin, Angelica; Moth‐Poulsen, Kasper; Hyldgaard, Per; Erhart, Paul
Abstract: Molecular photoswitches capable of storing solar energy are interesting candidates for future renewable energy applications. Here, using quantum mechanical calculations, we carry out a systematic screening of crucial optical (solar spectrum match) and thermal (storage energy density) properties of 64 such compounds based on the norbornadiene–quadricyclane system. Whereas a substantial number of these molecules reach the theoretical maximum solar power conversion efficiency, this requires a strong red‐shift of the absorption spectrum, which causes undesirable absorption by the photoisomer as well as reduced thermal stability. These compounds typically also have a large molecular mass, leading to low storage densities. By contrast, single‐substituted systems achieve a good compromise between efficiency and storage density, while avoiding competing absorption by the photo‐isomer. This establishes guiding principles for the future development of molecular solar thermal storage systems. Abstract : Finding the balance : Electronic structure calculations are employed to determine strategies and identify substituents that can enhance the performance of norbornadiene‐based molecular solar thermal storage systems. Focusing on solar spectrum match and storage density, the properties of 64 compounds are scanned. The champion compounds can achieve high storage densities and very good solar thermal match with the prospect of mid‐ to long‐term thermal stability.